Hubungan Lama Penggunaan Gadget terhadap Perkembangan Sosial pada Anak Prasekolah di TK Tunas Mekar Sari, Denpasar - Gusti Ayu Made Landhevi Paramasanthi; Ni Putu Diah Witari; Ni Putu Indah Kusumadewi Riandra (Aesculapius Medical Journal, 2024)
[The Relationship Between Duration of Gadget Use and Social Development in Preschool Children at Tunas Mekar Sari Kindergarten, Denpasar] The term "children's social development" describes how children change their behaviors as they grow to conform to the norms of their society. The social development of preschool children becomes complicated due to the effects of gadget use. In general, technology has the potential to enhance children's communication, social circles, and educational opportunities. However, children's social development may be negatively impacted by excessive gadget use. The objective of this study is to investigate the relationship between the duration of gadget use and the social development of preschool children. This research employs an analytical correlation with a cross-sectional approach, involving 82 parent respondents selected through consecutive sampling. Information was gathered by asking parents to complete a survey about their children's social development and the duration of their gadget use. The relationship between the length of gadget use and the social development of the children was analyzed using the chi-square test (p < 0.05). The majority of children were 6 years old (57.3%), and most parents held a bachelor's degree (33.8%) and worked in the private sector (53.7%). Most children's social development was categorized as poor (65.9%), and they used gadgets for a long time (64.6%). The results of this study also indicate a statistically significant relationship between the length of gadget use and the social development of preschool children at Tunas Mekar Sari Kindergarten in Denpasar (p < 0.001). The longer the children used gadgets, the poorer their social development.